The Evolution and Impact of Autonomous Systems: A Technical Analysis - Anusha Akkiraju (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores the evolution and impact of autonomous systems across various industrial sectors. The article explores the integration of artificial intelligence, machine learning, robotics, and advanced sensor networks in creating sophisticated autonomous platforms. It details the core architectural components, including perception systems, decision-making frameworks, actuation and control mechanisms, and communication infrastructure. The article covers practical applications in transportation, healthcare, manufacturing, and agriculture, demonstrating significant improvements in efficiency, safety, and operational capabilities. The article also addresses critical technical challenges, ethical considerations, and future directions for autonomous system development, emphasizing the importance of reliability, adaptability, and human-machine interaction.